P33 Serum total cortisol and plasma free cortisol response after low dose short synacthen test in stable cirrhosis. (6th September 2011) - Fede, G; Spadaro, L; Tomaselli, T; Privitera, G; Scicali, R; Vasianopoulou, P; Martin, N; Thomas, M; Purrello, F; Burroughs, A K
Abstract : Introduction: Adrenal Insufficiency (AI) defined by low dose short synacthen test (LDSST) in stable cirrhosis is frequent using serum total cortisol (TC). However no published data exist on directly measured plasma free cortisol (FC) after LDSST. Aim: We prospectively assessed adrenal insufficiency defined by LDSST in stable cirrhosis using TC and FC. Method: Patients with stable cirrhosis without shock and/or sepsis were prospectively studied using the LDSST. AI was defined by a peak-TC <494 mmol/l (Criterion 1) and a peak-FC <33 nmol/l (Criterion 2) 30 min after injection of 1 μg of tetracosactrin (Synacthen). Results: 78 consecutive patients with cirrhosis were studied (Viral: 16, Alcoholic: 41; other: 21). Basal TC (365±192 mmol/l) and peak TC (571±216 mmol/l) were significantly related to basal FC (26±24 nmol/l) and peak FC (53±34 nmol/l) respectively: for baseline values R=0.78, p<0.001, and for peak values R=0.70, p<0.05. Similar results were found considering only patients with hypoalbuminemia (albumin <25 g/l, 7 patients): for basal value R=0.88, p<0.001; for peak value R=0.89, p<0.05. Prevalence of AI was 35% (27/78) using total cortisol (Criterion 1) and 28% (22/78) using free cortisol (Criterion 2). There was agreement between total cortisol (Criterion 1) and free cortisol (Criterion 2) in 63 tests, in 10 AI was diagnosed only according TC (Criterion 1), and in 5 only according FC (Criterion 2): κ-coefficient 0.56, p<0.05. In the group with discordant tests patients had more advanced liver disease (Child score: 9.17±2.2 vs 7.66±1.9, p=0.03), lower basal TC (237±104 vs 395±196 mmol/l, p=0.03), and peak TC (464±121 vs 597±226 mmol/l, p=0.009). Conclusion: AI defined by LDSST is frequent in stable patients with cirrhosis, using both total cortisol and free cortisol criteria. However in patients with more advanced liver disease and/or low total cortisol level, discrepancy exists between the rates of diagnosis of AI using the total and free cortisol criteria. Thus in these patients AI should be confirmed by free cortisol measurement.